Epistemological Foundations Of Early Legal Utilitarianism - Kolosov, Igor; Sigalov, Konstantin Elizarovich (Տիգրան Մեծ)
This article analyzes the aggregate of reality cognition methods used in certain theories in the history of ethics and legal thought that are based on the principle of utility. The objective of this article is to pro-vide a full study of the methodology of the utilitarianism to determine its place in the establishment of le-gal utilitarianism. The article used methods of formal logic and specific methods such as the historical method.The main result of the article is the origins of utilitarianism is conditioned, inter alia, by the synthesis of the empirical and theoretical methodology. Heretofore, the application of purely empirical or purely theoretical methodologies for considering the state and legal phenomena through the prism of utility did not lead to the creation of branch of philosophy, economic or legal thought – utilitarianism.The main conclusion of this article is that the ―moral arithmetic‖ created under classical utilitarianism and later developed in the contemporary utilitarianism, based on which it is possible to compute the utility of this or that action (the totality of actions), contradicts such universal legal values as justice, defence, en-forcement of rights and freedoms, the principle of equality, and the moral values, and, therefore, cannot be supported.
Keywords: Epistemology